FORMS OF ORAL AND SPEECH ACTIVITY IN RUSSIAN LESSONS - Muratov Kamilzhan (Galaxy International Interdisciplinary Research Journal, 2022)
The article considers the forms of oral-speech activity in the Russian language classes, an analysis of the improvement and assimilation of materials is made.